Análise do comportamento à flexão de vigas em madeira reforçadas com barras de GFRP - Hoppe, Luciana Fernandes (2023)
Wood is a natural material originating from renewable sources, thus representing an ecologically conscious and sustainable option for use in constructions. Due to its mechanical properties, it finds a wide range of applications in the construction industry. However, it can exhibit natural defects that affect its mechanical properties, in addition to limitations in its commercial dimensions. In this regard, this study analyzed the bending behavior of wood beams of the Conifer (Cedar - Erisma uncinatum) and Dicotyledon (Pine - Pinus elliottii) types, reinforced with bars made of Glass Fiber Reinforced Polymer (GFRP), compared to reference (unreinforced) beams of the same woods. This is an explanatory and experimental research that subjected 12 specimens of each type of wood to the standardized test of parallel-to-grain compression, aiming at a simplified wood characterization and obtaining its strength class. The experimental program followed with the development of standardized four-point bending tests on a sample of 20 wood beams, tested to failure under load, to analyze their bending behavior. The 20 tested beams had dimensions of 45 mm x 90 mm x 1100 mm, with 5 Cedar beams and 5 Pine beams without reinforcement to establish reference values; 5 reinforced Cedar wood beams and 5 reinforced Pine wood beams. The beams were reinforced using the Near Surface Mounted (NSM) technique, where GFRP bars were fixed to the wood beams using epoxy adhesive, inserted into a groove made on the lower face's center (tension zone). The results showed that the reinforced beams exhibited better bending performance than the reference beams for both types of wood analyzed. Thus, it was possible to conclude that there was an improvement in the bending performance of the wood beams that received reinforcement bars, by approximately 8% for a 0.5% reinforcement ratio in Cedar wood, and around 40% for a 0.5% reinforcement ratio in Pine wood. The development of this research allowed us to affirm that the use of GFRP composite bars as reinforcement in wood beams can be a solution to the challenges related to their dimensions, contributing to the increased lifespan of the structure, which might be susceptible to deterioration or damage.